Enhancing magnetic particle testing of automotive parts - Hrairi, Meftah; Echrif, Salah B. M. (IIUM Press, 2011)
The principle disadvantage in magnetic particle inspection, as generally practiced today, is the combination of variable human judgment and interpretation, and variations in the critical components' characteristics which are: magnetic particle liquid sensitivity, ultraviolet intensity variations, and magnetic field variations at the surface of the test piece. In high speed inspection systems, these variables can reduce the reliability of magnetic particle inspection flaw detection to only about 70% [I]. What is needed is an online, heavy duty, high speed parts inspection with online documentation and almost perfect flaw detect ability within calibrated equipment, if possible, by using modem electronic systems. Currently, the automated MT systems are still in their first stages and are developed on individual researchers' basis [2]. Also, the few current systetns in the market which can automatically perform magnetic particle testing are extremely expensive. Hence, the need to provide a reasonable automated MT system with a comparable performance for inspecting surface defects in ferromagnetic materials automotive components